Pengaruh Cahaya Light Emiting Diode (LED) di Malam Hari terhadap Kortisol Serum dan Parameter Hematologi pada Tikus Wistar Jantan - Arief, Nila Ardilla; Arsyad, Aryadi; Idris, Irfan (Jurnal Kesehatan, 2021)
This modern era has changed the pattern of how humans do their daily activities in 24 hours. The pattern change includes time-shifting, most human activities now are performed at night. The consequences of the changes in human activities pattern and the increase of artificial lighting use in the night were assumed unhealthy, but how the mechanism worked was not identified yet. This was an experimental study conducted on male Wistar rats aged 12-16 weeks which were divided into 4 categories: 1 intervention group exposed for 15 days, 1 intervention group exposed for 30 days, and 2 control groups for each time exposure, light intensity 1200lux. At the end of exposures, the blood samples were taken from rats that had been anesthetized before by using ether. Then blood samples were taken to analyze their cortisol levels usingÂ the Enzyme-linked immunosorbent assayÂ (ELISA) method and the hematology was examined through autoanalyzer Abaxis. The data were analyzed using an independent T-test and Mann-Whitney test and considered significant if p-value<0,05. Overall, the cortisol and hematology levels indicated, especially Red Blood Cell (RBC), Mean Corpuscular Hemoglobin Concentration (MCHC), and neutrophil specifically for the group which had been exposed by LED lighting for 30 days.Â